2014
DOI: 10.1155/2014/830374
|View full text |Cite
|
Sign up to set email alerts
|

P2Y Receptor Modulation of ATP Release in the Urothelium

Abstract: The release of ATP from the urothelium in response to stretch during filling demonstrates the importance of the purinergic system for the physiological functioning of the bladder. This study examined the effect of P2 receptor agonists on ATP release from two urothelial cell lines (RT4 and UROtsa cells). Hypotonic Krebs was used as a stretch stimulus. Incubation of urothelial cells with high concentrations of the P2Y agonist ADP induced ATP release to a level that was 40-fold greater than hypotonic-stimulated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The quantity of released ATP (≈700 pmol/g tissue) is 10 to 100‐fold higher than many studies using bladder or mucosal strips , although others have reported similar values when care was taken to isolated the mucosa . Our values are also five to 1000‐fold greater than those from cultured urothelial cells exposed to hypotonic solutions, which further highlights differences between primary and cultured cells . These experiments also suggest that all three types of urothelial cell release similar quantities of ATP per unit surface area.…”
Section: Discussionsupporting
confidence: 57%
“…The quantity of released ATP (≈700 pmol/g tissue) is 10 to 100‐fold higher than many studies using bladder or mucosal strips , although others have reported similar values when care was taken to isolated the mucosa . Our values are also five to 1000‐fold greater than those from cultured urothelial cells exposed to hypotonic solutions, which further highlights differences between primary and cultured cells . These experiments also suggest that all three types of urothelial cell release similar quantities of ATP per unit surface area.…”
Section: Discussionsupporting
confidence: 57%
“…More specifically, ADP has been demonstrated to evoke ATP release from the urothelium, whereas adenosine inhibits ATP release via A1 receptors 98,102 . The urothelium also expresses diverse purine and pyrimidine receptor subtypes enabling distinct signal transduction 103106 . The activation of P2Y, but not P2X, receptors on the urothelium causes ATP release, suggesting urothelial P2Y receptors might contribute to purinergic neurotransmission 103,107 .…”
Section: Atp and Purinergic Receptorsmentioning
confidence: 99%
“…The urothelium also expresses diverse purine and pyrimidine receptor subtypes enabling distinct signal transduction 103106 . The activation of P2Y, but not P2X, receptors on the urothelium causes ATP release, suggesting urothelial P2Y receptors might contribute to purinergic neurotransmission 103,107 . However, P2X 2 and P2X 3 receptor expression is altered in urothelium from patients with interstitial cystitis indicating that P2X receptors are involved in urinary bladder sensory transduction in bladder injury or disease 105 .…”
Section: Atp and Purinergic Receptorsmentioning
confidence: 99%
“…Cells were then centrifuged through 10% bovine serum albumin (4000×g for 3 min), and cell-free supernatants were stored in duplicate at −20°C until required. ATP concentrations in supernatants were assessed using a Bioluminescence ATP Assay Kit (Sigma-Aldrich) as described [23]. The amount of lactate dehydrogenase (LDH) in supernatants was determined using a Cytotoxicity Detection Kit PLUS (LDH) (Roche Diagnostics) as per the manufacturer's instructions using a Molecular Devices (Sunnyvale, CA, USA) Spectramax Plus 384 plate reader.…”
Section: Atp Release Assaymentioning
confidence: 99%